CHILDREN AND COMMITMENT (Fiep Bulletin - online, 2012)
The paper aims at demonstrating that the commitment to achieving a better world for the children willnecessarily have to face the challenges imposed by serious threats to humanity in our days, such as thedestruction of biodiversity, explained by deforestation, climatic changes and the water problem; the demographicproblem, especially the bad distribution of income and the infant mortality; the problem of education and its newperspective of continuous education and the digital illiteracy; and the problems faced by children, such as childlabor and unavailability of health services.As ways to achieve this improvement in the life quality of children and future generations, the paperindicates: (i) the development of a Culture of Peace, tirelessly defended by the UN and UNESCO, and (ii) thecontinuous and appropriate use of Physical Education, whose concept, published in the World Manifesto ofPhysical Education FIEP 2000, promotes the development of an active lifestyle for youths and the children, andthe use of Sports, considered by the International Charter of Physical Education and Sport (UNESCO, 1978) aright of all individuals including Sport-Education, Sport-Leisure and Sport-Performance.
Keywords: education; contemporary problems; sport; physical education.